From vision to practice: Adoption of artificial intelligence in libraries across ASEAN - Xu, Yi-Shuai; A.M.K., Yanti Idaya; Kassim, Muhammad Shahreeza Safiruz (Malaysian Journal of Library and Information Science, 2025)
This study examines the use of artificial intelligence (AI) in libraries across ASEAN countries, focusing on national strategic support, AI implementation, and key challenges and opportunities in the regional context. Using a content analysis approach based on the Technology Organisation Environment (TOE) framework, 115 official documents including national AI strategies, policy reports, and statements were analysed. AI applications were reviewed at the institutional level by selecting the top five universities in the QS World University Rankings in each ASEAN country. Singapore and Malaysia show strong support for AI policies, while Indonesia, the Philippines, Thailand, and Vietnam show moderate commitment with established national policies. Brunei, Cambodia, Laos, and Myanmar exhibit emerging support, with AI mentioned only within a broader digital agenda. In practice, libraries in Singapore, Malaysia, Indonesia, Thailand, the Philippines, and Vietnam have adopted AI technologies or developed AI-enabled services for research and patron engagement, supported by training and investment in infrastructure. The introduction of AI is limited or undocumented in Brunei, Laos, Cambodia, and Myanmar. Major challenges include uneven technical resources, data quality issues, lack of governance, talent shortages, and inadequate ethical guidelines. Opportunities exist in local innovation, regional collaboration, policy advocacy, and training to accelerate AI adoption. This is the first region-wide analysis linking ASEAN national AI policies to AI implementation in libraries. It provides cross-country insights and practical cases for policymakers, library professionals, and regional bodies, and serves as a strategic reference to drive AI integration across the region.